Indikacije za operacijo sive mrene - Pfeifer, Vladimir (Zdravniški vestnik, 2005)
Background. Cataract surgery is the most performed surgical procedure in ophthalmology and medicine in general in developed countries. We were interested in indications and other factors influencing decision about surgical cataract treatment in developed world. Conclusions. The review of theliterature showed that there are significant differences in threshold or indications for cataract surgery even in the developed countries. The decisionto perform cataract surgery is mostly associated with central visual acuity.
Keywords: Cataract; Cataract Extraction; Katarakta; Katarakta, ekstrakcija; očesne bolezni; oftalmologija; operativno zdravljenje; siva mrena; Vid, ostrina; Visual Acuity